JADID DRAMAS AND THEIR ETHNOCULTURAL VALUES (American Journal of Interdisciplinary Research and Development, 2023)
This article talks about the formation of national ideology and culture in the beginning of the 20th century, the introduction of modern ideas, the struggle to achieve freedom and to have a new school system.